Prevalence of Hypertension among Medical Workers at Tishreen University Hospital - بلة, حسام; شريتح, أحمد; إبراهيم, همام (Latakia University Journal -Medical Sciences Series, 2020)
Objective: identifying prevalence of hypertension (HTN) among medical workers at Tishreen university hospital and relationship between HTN and variables (age, sex, BMI, smoking, Physical activity and stress). Methods and patients: the sample of study was 368 participants from health workers at Tishreen university hospital Lattakia 2019-2020. We measured Blood pressure, calculated BMI, and investigated occupational stress by place of working (we considered participant that working at emergency department and ICU had (High stress) other departments (moderate stress) and clinics (low stress) we also asked about smoking and physical activity. Results: The mean age was 43 years (56,3%<45 years, 47,3%≥45 years), BMI: 47%, 27,7% and 25,3% normal, overweight and obese respectively, smokers 46,7%, 55,7% had low physical activity, 39,9 and 39,1 had moderate and sever occupational stress respectively, prevalence of HTN 28,8%, the rate of pressure control among those previously known to have HTN 31%, 80,2% of those with HTN were more than 45 years of age with likelihood 5,2 folds higher compared to those under the age of 45 years, 80% of those with HTN were overweight and obese with likelihood a 3,4 folds higher compared with normal weight, 84.9% of participants had low physical activity with likelihood 4,4 folds higher to developing HTN, 89,6 of those with HTN had a working stress between moderate and server with likelihood 2,3 folds compared to those with mild stress, we did not find a statistically significant relationship with gender or smoking. Conclusions: prevalence of HTN was high among health workers and control of HTN was low. The most significant relationship was between HTN with age and BMI.